IMPLEMENTASI KEPERAWATAN MENGONTROL HALUSINASI DENGAN MENGHARDIK - Sri Endriyani; Ira Kusumawaty; Marta Pastari; Winda Umaya (NHM PRESS, 2022)
Hallucinations are a problem with perceptual disorders that can cause a person's loss of ability to distinguish internal and external stimuli. This research is a descriptive study with a case study design using a comprehensive nursing process approach including assessment, diagnosis, planning, implementation and evaluation. The results of the study indicate that the implementation of rebuke implementation strategies in hallucinating patients is very helpful in controlling hallucinations. Rebuking hallucinations can reduce the appearance of hallucinations with diversion activities and increase the client's ability to focus and concentrate.